The BDNF Val66Met Polymorphism Has No Effect on Encoding-Related Hippocampal Response But Influences Recall in Remitted Patients With Bipolar Disorder - Hørlyck, Lone Diana; Macoveanu, Julian; Vinberg, Maj; Kessing, Lars Vedel; Siebner, Hartwig Roman; Miskowiak, Kamilla Woznica (Frontiers in Psychiatry, 2019)
Background: Cognitive impairments in bipolar disorder (BD) such as memory deficits are associated with poor functional outcomes and it has been suggested that the Val66Met polymorphism contribute to individual variability in memory function in BD. The current study investigated the relationship between the Val66Met polymorphism, neural activity during a picture-encoding task and subsequent memory recall. Methods: A total of 70 patients with bipolar disorder grouped according to genotype (ValVal or Met carriers (MetVal/MetMet)) underwent fMRI while performing a picture-encoding task. Memory for the encoded pictures was tested with a subsequent free recall memory task. Results: There was no difference between the ValVal homozygotes and Met carriers in the involvement of hypothesised memory encoding regions i.e. hippocampus and dorsal PFC. However, an exploratory whole-brain analysis showed greater encoding-related lateral occipital cortex activity in Met carriers. Behaviourally, Met carriers also showed better free recall of the encoded pictures. Conclusions: We found no effect of the BDNF genotype on encoding-related neural activity in BD although Met carriers showed superior memory performance after the scan.